Occurrence of Pain Syndrome Due to Osteoparosis in Patients with Breast Cancer - Sokhibova Z. R; Xalikova F. Sh (Research Parks Publishing LLC, 2021)
Today, specific treatment for breast cancer leads to a decrease in estrogen-sex hormones, as a result of which the reduction of bone marrow and the development of osteoporosis is an urgent problem for many patients. 150 women were interviewed to improve the efficiency of diagnosis of osteoporosis in order to identify osteoporosis and improve the quality of life of patients with breast cancer and pain syndrome of fertile age. Breast cancer was diagnosed in 101 (67.3%) women, osteoporosis and osteopenia were diagnosed in 49 (32.6%) women without breast cancer, pain syndrome was diagnosed in 76.6% of cases.